Molecular evidence and additional morphological characters to distinguish Ornithodoros brodyi and Ornithodoros yumatensis (Ixodida: Argasidae) in their different developmental stages - Guzman Cornejo, Carmen M.; Garcia-Prieto, Luis; Rebollo-Hernandez, Andrea; Nava, Santiago; Sanches-Montes, Sokani; Venzal, José Manuel (2017)
Ornithodoros brodyi and Ornithodoros yumatensis are two species distributed in the Americas and associated with bats and caves. Both species have similar morphology, and the diagnostic traits of adults have not been detailed or illustrated accurately. In this study, the independence of both species is validated on the basis of molecular evidence (using partial sequences of 16S rDNA gene), and the morphological differences between them (dentition of the hypostome and traits of individual mammillae) are confirmed through light and scanning electron microscopy. In addition to the above characteristics, we observed other traits that may serve to differentiate both species: dorsal setae are short and thick in O. yumatensis and are thin and moderate in size in O. brodyi. We also observed a conspicuous hood in O. brodyi, which was absent in O. yumatensis. Another characteristic observed is a line of setae, near the end of Tarsi II-IV, which in O. brodyi is formed by less than five setae and in O. yumatensis by more than five. The main morphological difference between larvae of the 2 species is the number of ventral setae [9 (4 circumanal pairs) in O. brodyi and 8 (3 circumanal pairs) in O. yumatensis]. The genetic divergence in 16S rDNA sequences between these two species ranges from 9.7 to 10.6%.